2012
DOI: 10.2190/om.65.1.d
|View full text |Cite
|
Sign up to set email alerts
|

Does Superstition Help? A Study of the Role of Superstitions and Death Beliefs on Death Anxiety Amongst Chinese Undergraduates in Hong Kong

Abstract: Past research has shown that traditional Chinese death beliefs, which mostly consisted of superstitious thoughts, are related to death anxiety. However, other studies have shown that superstitions may help people cope with uncertainty and, therefore, reduce uncertainty-induced anxiety. The role of superstitions, whether related to heightened death anxiety or reduced death anxiety, is unclear. This study attempted to address the knowledge gap by examining the relationships among superstitions and Chinese death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…The dimension also revealed that individuals’ might perceive POD as an inauspicious or a disturbing act to the dead. These perceptions may be related to the deeply rooted traditional death beliefs as well as one’s superstitions that individuals who have such perceptions may also have higher death anxiety as suggested in the past research (Wong, 2012). In addition, the Mutilation and Imperfectness dimension was found strongly correlated with the Detachment dimension, that being detached might also be a way of coping to avoid the emotional exhaustion in dealing with the concerns about organ donation (Sonnentag, Kuttler, & Fritz, 2010).…”
Section: Discussionmentioning
confidence: 80%
“…The dimension also revealed that individuals’ might perceive POD as an inauspicious or a disturbing act to the dead. These perceptions may be related to the deeply rooted traditional death beliefs as well as one’s superstitions that individuals who have such perceptions may also have higher death anxiety as suggested in the past research (Wong, 2012). In addition, the Mutilation and Imperfectness dimension was found strongly correlated with the Detachment dimension, that being detached might also be a way of coping to avoid the emotional exhaustion in dealing with the concerns about organ donation (Sonnentag, Kuttler, & Fritz, 2010).…”
Section: Discussionmentioning
confidence: 80%
“…Whereas South Asians, Chinese, and Latinx tend to express more explicit emotions, such as crying, than Whites (Inman et al, 2007;Neimeyer et al, 2003;Oltjenbruns, 1998). Chinese individuals may also exhibit higher death-related anxiety levels and are more superstitious than Whites or other ethnic minorities (Neimeyer et al, 2003;Wong, 2012). Superstition requires behaviors and beliefs that function within the realm of supernatural forces (Corsini, 2002).…”
Section: Ethnic-cultural Differencesmentioning
confidence: 99%
“…Regarding cultural context, death is a fearful subject in East Asia due to traditions such as shamanistic ancestor worship, Taoism, Buddhism, and Confucianism. East Asian people tend to be reluctant to bring up issues of death and loss for fear of invoking bad luck (Holland, 2008;Lee, Kim, Choi, & Koo, 2014;Wong, 2012Wong, -2013. Such sociocultural contexts may prevent researchers from closely investigating young children's understanding of concepts related to death and bereavement.…”
Section: Research On Children's Understanding Of Death and Lossmentioning
confidence: 99%